Determinants of Adoption of Soil and Water Conservation Practices in Ethiopia - Girmachew Siraw (Journal of Agricultural Extension Management, 2025)
This study, undertaken in the environs of Simen Mountain National Park of Amhara state attempts to identify determinants and extent of adoption of soil and water conservation technologies. Both qualitative and quantitative methods were used in the study. Descriptive statistics and a logistic model were employed to identify the factors, which determine adoption of soil and water conservation practices. It is evident from this study that socio economic and institutional factors influence the level of investment households commit to soil and water conservation. The result shows that the explanatory variables viz., the number of years the household made farming as a living, the total household labor and visit of the extension agent are significantly related to adoption of soil and water conservation practices by the farmers.